PAENIBACILLUS POLYMYXA IMB – B 8059 – ПРОДУЦЕНТ КАРБОНОВИХ КИСЛОТ І ФЕНОЛЬНИХ СПОЛУК - Токмакова, Л. М.; Хархота, М. А. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2026)
Objective. To study the ability of secondary metabolite production — carbonic acids and phenolic compounds — by the bacterium Paenibacillus polymyxa IMB – B 8059. Methods. P. polymyxa was cultivated in a liquid nutrient medium containing corn extract and molasses on a microbiological shaker (220 rpm) at 28 °C for 48 hours. The content of short-chain fatty acids in the P. polymyxa culture liquid was determined by gas chromatography–mass spectrometry using an Agilent 6890N/5973inert instrument (Agilent Technologies, USA). Extraction of phenolic compounds from the culture medium was performed using an Agilent Technologies 1200 liquid chromatograph. The identification and quantification of phenolic compounds were performed using standard solutions of phenolic acids (gallic, hydroxyphenylacetic, chlorogenic, caffeic, syringic, p-coumaric, transferulic, sinapic, trans-cinnamic, and quinic acids). Results. The levels of carbonic acids and phenolic compound synthesis by P. polymyxa IMB – B 8059 were determined. The following carbonic acids were detected in the culture medium: acetic acid — 415.35 μg/mL, and in insignificant amounts, butanoic acid — 9.13 μg/mL and propanoic acid — 7.52 μg/mL. It was shown that the strain demonstrates the ability to synthesize phenolic compounds: hydroxyphenylacetic acid — 318.86 μg/mL, caffeic acid — 32.96 μg/mL, syringic acid — 800.24 μg/mL, benzoic acid — 1168.86 μg/mL, sinapic acid — 257.23 μg/mL, and trans-cinnamic acid — 468.32 μg/mL. Conclusions. P. polymyxa IMB – B 8059 synthesizes a significant amount of carbonic acids and phenolic compounds, which may play an important role in the processes of forming interactions with plants and microorganisms in the root zone. This largely explains the mechanism of the bacterium’s effect on the transformation of phosphorus compounds in the rhizosphere soil, the improvement of plant phosphorus nutrition, and the optimization of crop production when pre-sowing seed inoculation is performed.